Pengaruh Media Pakan Baki (CFT) dan Baby Chick Feeder (BCF) terhadap Konsumsi Pakan, Pertambahan Berat Badan Harian dan Konversi Pakan pada Ayam Ras Pedaging - Iwan Iwan; Herawati M; Rastosari A (Wahana Peternakan, 2018)
The aim of this study was to determine the effect of feed media on feed intake, average daily gain, and feed conversion ratio. The research method used in this study is the experimental method, which is the type of research used to find the effect of certain treatment against others in controlled conditions. This research was conducted on poultry breeding farm at Company Farm. The division was located in Pembagian village, Tanjung Bintang Subdistrict, South Lampung Regency. This study was carried out for 18 days from broiler aged 0 to 18 days. Method of data collection used in this research using instrument that is observation sheet to get feed intake, average daily gain (ADG), and total weight. The data obtained were analyzed by using independent sample t-test test with SPSS version 17.00 software. The result showed that feed media used had a significant effect on feed conversion, but no significant effect on feed intake and average daily gain (ADG). The feed conversion in broiler maintained with Baby Chick Feeder (BCF) was better than Chick Feeder Tray (CFT). Feed intake and average daily gain (ADG) of broiler chickens maintained with Baby Chick Feeder (BCF) was similar to feed intake and average daily gain (ADG) of broiler maintained with Chick Feeder Tray (CFT). Keywords: Average Daily Gain, Baby Chick Feeder, Chick Feeder Tray, Feed Intake, Feed Conversion Ratio